A slow transcription rate causes embryonic lethality and perturbs kinetic coupling of neuronal genes. (15th April 2019) - Maslon, Magdalena M; Braunschweig, Ulrich; Aitken, Stuart; Mann, Abigail R; Kilanowski, Fiona; Hunter, Chris J; Blencowe, Benjamin J; Kornblihtt, Alberto R; Adams, Ian R; Cáceres, Javier F
Abstract: The rate of RNA polymerase II (RNAPII) elongation has an important role in the control of alternative splicing (AS); however, the in vivo consequences of an altered elongation rate are unknown. Here, we generated mouse embryonic stem cells (ESCs) knocked in for a slow elongating form of RNAPII. We show that a reduced transcriptional elongation rate results in early embryonic lethality in mice. Focusing on neuronal differentiation as a model, we observed that slow elongation impairs development of the neural lineage from ESCs, which is accompanied by changes in AS and in gene expression along this pathway. In particular, we found a crucial role for RNAPII elongation rate in transcription and splicing of long neuronal genes involved in synapse signaling. The impact of the kinetic coupling of RNAPII elongation rate with AS is greater in ESC‐differentiated neurons than in pluripotent cells. Our results demonstrate the requirement for an appropriate transcriptional elongation rate to ensure proper gene expression and to regulate AS during development. Synopsis: Transcription elongation rates have a regulatory role in the expression of genes and the regulation of their alternative splicing patterns during development. A slow RNA polymerase II (RNAPII) mutant allele (R749H) causes early embryonic lethality in mice. A slow RNAPII impairs ESCs differentiation towards the neural lineage. It limits neural stem cells (NSC) renewal in vitro and preferentially affects transcription and AS of long neuronal genes. The impact of the kinetic coupling of RNAPII elongation rate with Alternative splicing (AS) is greater in ESC‐differentiated neurons than in pluripotent cells. Abstract : RNA polymerase II elongation rates play key roles in expression and alternative splicing patterns of genes, with notably higher impact in neurons differentiating from embryonic stem cells than in pluripotent cells.